2017
DOI: 10.1103/physrevfluids.2.123302
|View full text |Cite
|
Sign up to set email alerts
|

Silo outflow of soft frictionless spheres

Abstract: Outflow of granular materials from silos is a remarkably complex physical phenomenon that has been extensively studied with simple objects like monodisperse hard disks in two dimensions (2D) and hard spheres in 2D and 3D. For those materials, empirical equations were found that describe the discharge characteristics. Softness adds qualitatively new features to the dynamics and to the character of the flow. We report a study of the outflow of soft, practically frictionless hydrogel spheres from a quasi-2D bin. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 30 publications
7
60
0
Order By: Relevance
“…In contrast, the flow velocity of the soft HGS decreases noticeably with progressing discharge of the container. This is in accordance with earlier qualitative observations in 2D containers [4], where it was found that the pressure near the outlet is nearly hydrostatic for HGS, and lower pressure leads to a reduced outflow rate.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, the flow velocity of the soft HGS decreases noticeably with progressing discharge of the container. This is in accordance with earlier qualitative observations in 2D containers [4], where it was found that the pressure near the outlet is nearly hydrostatic for HGS, and lower pressure leads to a reduced outflow rate.…”
Section: Discussionsupporting
confidence: 93%
“…Silo discharge experiments in 2D containers with hydrogel spheres swollen in distilled water (9.2 mm diameter) have been reported before [4]. These experiments demonstrated qualitative differences of the discharge dynamics through narrow orifices as compared to rigid spheres.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations